PENGEMBANGAN HANDOUT BERBASIS GAMBAR PADA MATERI SISTEM PERNAPASAN MANUSIA UNTUK SMP - Masratika, Masratika; Risdawati, Renny; Ardi, Ardi (Pendidikan Biologi, 2013)
ABSTRACTAppropriate use of instructional materials in the learning process can improve the understanding, interest, and motivation of students to learn. Many things can teachers do to help students achieve better learning outcomes, one of them by developing teaching materials of interest. Handout that based image is one of the teaching materials to enable students to understand the biology material. This research aims is to produce valid Handout that based image on the material and practical human respiratory system for SMP. This research is a development by using the 4-D model of the development comprising the steps of define, design, develop and disseminate. Phase disseminate not done due to limited funds and time that the author had. The results of this development is to produce a handout with a picture-based criteria are very valid and very practical.